Emetophobia: A case of nausea leading to dehydration in an adolescent female. (August 2020) - Kannappan, Anju; Middleman, Amy B
Emetophobia is defined as the specific fear of vomiting and avoidance behaviors related to vomiting situations; the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition, specifies this condition as a Specific Phobia: Other type: Vomiting (SPOV). Our case report describes an adolescent presenting with medical complications, specifically notable dehydration, due to new onset Specific Phobia: Other type: Vomiting after experiencing a bout of viral gastroenteritis. In this patient's case, her severe anxiety served as the root cause for a significant decrease in her quality of life for a year and was not identified by healthcare providers until after an extensive medical workup had taken place. Treatment involved alleviating her dehydration with slow introduction of foods with high water content into her diet and addressing her anxiety with hydroxyzine as a short-term intervention and a selective serotonin reuptake inhibitor for long-term management. This treatment plan allowed for our patient's symptoms to resolve over the course of a few months and she was able to return to her usual activities of daily living. With discussing emetophobia, this case highlights a topic that is not largely discussed in the literature surrounding adolescent health.